The insect molecular clock. Issue 2 (16th February 2013) - Ho, Simon Y W; Lo, Nathan
Abstract: Estimating the timescale of evolution forms an important component of many molecular studies of insects. By obtaining date estimates for significant evolutionary events, we can gain a better understanding of biological processes such as diversification and adaptation. Evolutionary timescales can be estimated from genetic sequence data using the molecular clock, which was proposed five decades ago and has subsequently undergone considerable development. In this article, we provide a summary of the theoretical basis of the molecular clock, including its relationship to the neutral and nearly neutral theories of molecular evolution. We explain how the clock can be used to estimate evolutionary timescales from DNA and protein sequence data. Finally, we describe some of the key challenges facing users of the molecular clock in studies of insects, including the problems of rate variation among lineages and over time.